ریاست مدینہ کےاستحکام میں بیت المال کاکردار: سیرت طیبہ کی روشنی میں : The role of Bait-ul-Mal in the stability of the state of Madinah in the Light of Seerah Tayyeba - Dr. Ahmad Raza,; Dr. Syed Waheed Ahmad, (MEI, 2023)
The treasury of the Muslim state or the special treasury of the Islamic empire which the Islamic government spends for the welfare of the common people. The treasury is both the bank of the Muslim people and the national treasury. Also the guarantor of the property, the institution of commerce, the protector of the trust and the public treasury of the central institution of the Muslims. Given the sources and uses of the treasury, the concept of the treasury is that the existence of a public treasury is necessary for the government of Rabbani (Islamic caliphate) to use the economic system of Islam. The safe haven of this treasury is called the treasury and although sometimes the treasury is widely applied to the entire financial system, in general terms it is applied to the safe place of the central treasury. The treasor is spent on the welfare of Muslims. The role of Bait-ul-Mal has been the most important factor in the stability of the state of Madinah since the time of the Prophet (PBUH) and this role will continue forever in Islamic states.